2022
DOI: 10.2147/por.s361907
|View full text |Cite
|
Sign up to set email alerts
|

A Phase IV Study on Safety, Tolerability and Efficacy of Dolutegravir, Lamivudine, and Tenofovir Disoproxil Fumarate in Treatment Naïve Adult Indian Patients Living with HIV-1

Abstract: Purpose WHO recommends dolutegravir (DTG) based regimens as first-line treatment for HIV-1 infection. However, few studies have been conducted in Indian population. Hence, our study evaluated the safety, tolerability, and efficacy of DTG 50 mg with Tenofovir and Lamivudine (300/300mg) fixed dose combination in treatment naïve adult Indian patients. Methods This was an open label, multicenter, prospective, interventional, phase IV study conducted across 14 sites between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…We observed that ALH were more likely to need to attend a clinic during school time, likely as clinics do not consider aligning day school ALH clinic visits with school schedules. With once-daily DTG-based regimens, 31,32 adjusting medication timing to fit the school schedules is feasible. We recently identified that schools in Kenya lack medication use policies making it challenging to ensure access when needed.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that ALH were more likely to need to attend a clinic during school time, likely as clinics do not consider aligning day school ALH clinic visits with school schedules. With once-daily DTG-based regimens, 31,32 adjusting medication timing to fit the school schedules is feasible. We recently identified that schools in Kenya lack medication use policies making it challenging to ensure access when needed.…”
Section: Discussionmentioning
confidence: 99%
“…Với các nghiên cứu về tác dụng của DTG cho người nhiễm HIV lần đầu điều trị, kết quả tháng thứ 6 về lượng virus HIV giảm dưới ngưỡng phát hiện chiếm tỉ lệ 86,8%, cao hơn so với kết quả của chúng tôi (78,2%), nhưng lượng virus HIV ban đầu của bệnh nhân nghiên cứu chúng tôi cao hơn, và ngưỡng phát hiện là 20 bản sao/mL và CD4 tăng thêm 143 tế bào 5 cũng tương đương như của nghiên cứu chúng tôi là tháng thứ 6 tế bào CD4 tăng thêm 162 tế bào/mm 3 .…”
Section: Nghiên Cứu Khoa Họcunclassified
“… 5 , 6 DTG with two Nucleoside Reverse Transcriptase Inhibitors (NRTIs) has shown significant efficacy in HIV suppression in individuals. 7 , 8 DTG-based regimens may be more effective for CD4 recovery and virologic suppression than EFV-based regimens, making them a preferred treatment option for initial HIV treatment. 9 DTG also has fewer drug interactions than EFV, a better genetic barrier to developing drug resistance, and is particularly effective against HIV-2 infection, which is inherently resistant to EFV.…”
Section: Introductionmentioning
confidence: 99%